a. (3.2 x 10^4) + (1.95 x 10^6) = 1.95 x 10^6
b. (1.95 x 10^6) - (3.2 x 10^4) = 1.9468 x 10^6
c. (3.2 x 10^4) * (1.95 x 10^6) = 6.24 x 10^10
d. (1.95 x 10^6) / (3.2 x 10^4) = 60.9375 x 10^1 = 6.09375 x 10^2
U4L10: PORTFOLIO (modified)
ONLY DO PROBLEM #1 and follow questions a-d only put answers in correct scientific notation. NO NEED TO DO IT ALL…use 3.2x10^4 and 1.95 x 10^6 for steps a,b,c,d. That is it for my portfolio. ANSWERS MUST BE IN SCIENTIFIC NOTATION!!!!
a. Add 3.2 x 10^4 and 1.95 x 10^6
b. Subtract 1.95 x 10^6 and 3.2 x 10^4
c. Multiply 3.2 x 10^4 and 1.95 x 10^6
d. Divide 1.95 x 10^6 and 3.2 x 10^4
5 answers
1. incorrect..sum is not difference
2.incorrect it is not a -1.918
3 and 4 look good
2.incorrect it is not a -1.918
3 and 4 look good
I apologize for the mistakes. Let me correct them:
a. To add 3.2 x 10^4 and 1.95 x 10^6:
3.2 x 10^4 + 1.95 x 10^6
To add the numbers, we need to convert one of them to have the same exponent as the other. Let's convert 3.2 x 10^4 to have the same exponent as 1.95 x 10^6. By multiplying 3.2 by 10^2, we get:
3.2 x 10^4 = 320 x 10^2
Now we can add the numbers:
320 x 10^2 + 1.95 x 10^6 = 32000 x 10^2 + 1.95 x 10^6
Combining the coefficients, we get:
32000 + 1.95 = 32295
The exponent remains the same since we are adding numbers in scientific notation. Therefore, the result is:
3.2295 x 10^4.
b. To subtract 1.95 x 10^6 and 3.2 x 10^4:
1.95 x 10^6 - 3.2 x 10^4
Again, let's convert 3.2 x 10^4 to have the same exponent as 1.95 x 10^6:
3.2 x 10^4 = 320 x 10^2
Now we can subtract the numbers:
1.95 x 10^6 - 320 x 10^2 = 1950 x 10^4 - 320 x 10^2
Combining the coefficients, we get:
1950 - 0.032 = 1949.968
The exponent remains the same since we are subtracting numbers in scientific notation. Therefore, the result is:
1.949968 x 10^6.
c. To multiply 3.2 x 10^4 and 1.95 x 10^6:
We need to multiply the coefficients and add the exponents:
(3.2 x 1.95) x (10^4 x 10^6) = 6.24 x (10^4+6) = 6.24 x 10^10.
Therefore, the result is 6.24 x 10^10.
d. To divide 1.95 x 10^6 by 3.2 x 10^4:
We need to divide the coefficients and subtract the exponents:
(1.95 / 3.2) x (10^6 / 10^4) = 0.609375 x (10^6-4) = 0.609375 x 10^2.
Therefore, the result is 0.609375 x 10^2, or in scientific notation, 6.09375 x 10^1.
a. To add 3.2 x 10^4 and 1.95 x 10^6:
3.2 x 10^4 + 1.95 x 10^6
To add the numbers, we need to convert one of them to have the same exponent as the other. Let's convert 3.2 x 10^4 to have the same exponent as 1.95 x 10^6. By multiplying 3.2 by 10^2, we get:
3.2 x 10^4 = 320 x 10^2
Now we can add the numbers:
320 x 10^2 + 1.95 x 10^6 = 32000 x 10^2 + 1.95 x 10^6
Combining the coefficients, we get:
32000 + 1.95 = 32295
The exponent remains the same since we are adding numbers in scientific notation. Therefore, the result is:
3.2295 x 10^4.
b. To subtract 1.95 x 10^6 and 3.2 x 10^4:
1.95 x 10^6 - 3.2 x 10^4
Again, let's convert 3.2 x 10^4 to have the same exponent as 1.95 x 10^6:
3.2 x 10^4 = 320 x 10^2
Now we can subtract the numbers:
1.95 x 10^6 - 320 x 10^2 = 1950 x 10^4 - 320 x 10^2
Combining the coefficients, we get:
1950 - 0.032 = 1949.968
The exponent remains the same since we are subtracting numbers in scientific notation. Therefore, the result is:
1.949968 x 10^6.
c. To multiply 3.2 x 10^4 and 1.95 x 10^6:
We need to multiply the coefficients and add the exponents:
(3.2 x 1.95) x (10^4 x 10^6) = 6.24 x (10^4+6) = 6.24 x 10^10.
Therefore, the result is 6.24 x 10^10.
d. To divide 1.95 x 10^6 by 3.2 x 10^4:
We need to divide the coefficients and subtract the exponents:
(1.95 / 3.2) x (10^6 / 10^4) = 0.609375 x (10^6-4) = 0.609375 x 10^2.
Therefore, the result is 0.609375 x 10^2, or in scientific notation, 6.09375 x 10^1.
shorter
a. (3.2 x 10^4) + (1.95 x 10^6) = 1.95 x 10^6
b. (1.95 x 10^6) - (3.2 x 10^4) = 1.91768 x 10^6
c. (3.2 x 10^4) * (1.95 x 10^6) = 6.24 x 10^10
d. (1.95 x 10^6) / (3.2 x 10^4) = 6.09375 x 10^1
b. (1.95 x 10^6) - (3.2 x 10^4) = 1.91768 x 10^6
c. (3.2 x 10^4) * (1.95 x 10^6) = 6.24 x 10^10
d. (1.95 x 10^6) / (3.2 x 10^4) = 6.09375 x 10^1